Atividades antinociceptiva e antiinflamatória dos polissacarídeos sulfatados da alga marinha vermelha Gracilaria cornea J. Agardh - Coura, Chistiane Oliveira (2011)
Marine algae are natural sources of sulfated polysaccharides possessing several biological activities (anticoagulant, antithrombotic, antinociceptive, anti-inflammatory etc.) and that exhibit minimal toxicity and are considered of great interest to the pharmaceutical and food industries. This study aimed to evaluate the effects of sulfated polysaccharides total (SPT) from the red seaweed Gracilaria cornea (Gc) in classical models of animal experimentation. Swiss mice male (18-25g) and male Wistar rats (120-260g) in nociception and acute inflammation assays were used. The SPT-Gc yield extraction obtained by enzymatic digestion (6 h, 60 ° C) was 16.75 ± 0.98%. The SPT-GC was able to reduce (p<0.05) the number of writhing induced by 0.8% acetic acid (66.2, 65.3 and 96.3% for 3, 9 and 27 mg kg-1 (i.v.), respectively). In formalin test, the SPT-Gc inhibited (p<0.05) licking time in both phases of testing (56.1 and 93.2% first-phase, 88.2 and 98.0% second- phase for 9 and 27 mg kg-1 (i.v.), respectively), whereas the dose 3 mg kg-1 had only effect in the second phase of the trial. In the hot plate test, the antinociceptive effect of SPT-Gc were seen only in treatment with 27 mg kg-1 (i.v.). These tests in mice suggest that the analgesic effects occur through mechanism of action of central and peripheral. The model of peritonitis demonstrated that SPT-Gc exert effects on the migration of total leukocytes (52.7%) and neutrophils (59%) at a dose of 3 mg kg-1 (s.c.). On the other hand, the doses (3 and 9 mg kg-1, s.c.) appear able to inhibit the paw edema induced by carrageenan, particularly at the third hour, with the effects confirmed by MPO activity in paw tissue (p<0.05) and the occasional reduction (p<0.05) of paw edema of mice induced by dextran in the first hour at all doses tested. Finally, subchronic toxicity test was conducted in groups of 6 mice (males), which received: Saline (0.15 M, i.p.) and SPT-Gc (9 mg kg-1, i.p.) for 14 consecutive days. The results showed that the administrations of SPT-Gc did not show to differences in body mass (p>0.05). Additionally, the SPT did not produce changes in organ weights (heart, liver, kidney, spleen and thymus) in relation to body mass of animals, except the spleen (p<0.05), suggesting an immunomodulatory property. No change for liver biochemical tests (AST and ALT) or renal function was also observed (p>0.05), or on the hematological parameters (erythrocytes, hemoglobin, hematocrit, MCV, HGM, MCHC, leucocytes, lymphocytes, monocytes, neutrophils and platelets) considered, except hemoglobin (p<0.05). Therefore, the red seaweed Gracilaria cornea sulfated polysaccharides present security and antinociceptive and antiinflammatory activities